Fast charging station based on hybrid solar panels and Grid - Hidayat, Teguh; Dewi, Citra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The growing number of electric vehicles (EVs) has increased the demand for fast and sustainable charging infrastructure. Currently, most charging stations in Indonesia rely heavily on electricity from the national grid (PLN), resulting in high operational costs, especially during peak hours. On the other hand, the potential of renewable energy sources, such as solar power, has not been optimally utilized. This final project aims to design and develop a hybrid fast-charging station prototype that combines power sources from PLN (60%) and solar panels (40%). The system is designed to support the charging needs of electric motorcycles produced by PT Len Industri (Persero), using fast-charging technology that is efficient and environmentally friendly. Testing is conducted to ensure the system provides a fast, stable charging solution while reducing dependence on the conventional power grid. The results of this project are expected to contribute to the development of a more sustainable national electric vehicle infrastructure.